The Road to Metagenomics: From Microbiology to DNA Sequencing Technologies and Bioinformatics - Escobar-Zepeda, Alejandra; Vera-Ponce de León, Arturo; Sanchez-Flores, Alejandro (Frontiers in Genetics, 2015)
The study of microorganisms that pervade each and every part of this planet has encountered many challenges through time such as the discovery of unknown organisms and the understanding of how they interact with their environment. The aim of this review is to take the reader along the timeline and major milestones that led us to modern metagenomics. This new and thriving area is likely to be an important contributor to solve different problems. The transition from classical microbiology to modern metagenomics studies has required the development of new branches of knowledge and specialization. Here, we will review how the availability of high-throughput sequencing technologies have transform microbiology and bioinformatics and how we tackle the inherent computational challenges that arose from this DNA sequencing revolution. New computational methods are constantly developed to collect, process and extract useful biological information from a variety of samples and complex datasets but metagenomics needs the integration of several of these computational methods. Despite the level of specialization needed in bioinformatics, is important that life-scientists have a good understanding of it, for a correct experimental design that allow them to reveal the information in a metagenome.